An investigation into “leadership at all levels” in Scottish Schools - Holmes, Joanna (2017)
The publication of Teaching Scotland’s Future (Donaldson, 2011) was a catalyst for the re-conceptualisation of the Teaching Profession in Scotland. This research particularly focuses on the emphasis of “leadership at all levels” which has become prevalent in Scottish Educational Policy and Practice. Using a multi-case study approach, interviews were conducted in three schools across Scotland to explore how these policies and re-conceptualisations were being enacted; particularly in relation to informal leaders. Using previous research on the concept of Teacher Leadership as a basis (Holmes, 2016), an exploration of culture, relationships and resources was conducted and barriers and supports to the development of “leadership at all levels” were proposed. Although related to policy the case studies demonstrated the importance of the principal (referred to as head teacher) in being key to staff developing wider leadership roles. They also suggested that development of wider leadership does not always require a strategic decision or policy; rather it may develop through a preferred style of the principal or in response to a need within a context.